Preventing Foodborne Illness Associated with Clostridium perfringens - Keith R. Schneider; Renée Goodrich-Schneider; Michael A. Hubbard; Susanna Richardson (EDIS)
This is one in a series of fact sheets discussing common foodborne pathogens of interest to food handlers, processors, and retailers. This revised 5-page fact sheet was written by Keith R. Schneider, Renée Goodrich-Schneider, Michael A. Hubbard, and Susanna Richardson, and published by the UF Department of Food Science and Human Nutrition, January 2014.